1972
DOI: 10.1139/p72-286
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Models and Brillouin Scattering in a Molecular Gas

Abstract: Within the framework of the Wang Chang–Uhlenbeck kinetic equation, we propose a model description of molecular gases. The model is related to the models earlier discussed by Hanson and Morse. In our formulation, the model requires no adjustable parameters to analyze the light scattering spectrum from a molecular gas. We apply the model theory to recent Brillouin scattering experiments on hydrogen, deuterium, and hydrogen deuteride and find excellent agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
5

Year Published

1974
1974
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 7 publications
0
78
0
5
Order By: Relevance
“…Line shapes in spontaneous Rayleigh-Brillouin scattering ͑SRBS͒ have been predicted most succesfully [2][3][4] by the theoretical model developed by Boley et al 5 and Tenti et al 6 In this model, information regarding the Boltzmann collision integral is obtained from transport coefficients. Pan et al successfully extended the model of Boley et al 5 to predict coherent Rayleigh-Brillouin scattering ͑CRBS͒ and reported good agreement with experimental data on several monatomic and molecular gases.…”
Section: Introductionmentioning
confidence: 99%
“…Line shapes in spontaneous Rayleigh-Brillouin scattering ͑SRBS͒ have been predicted most succesfully [2][3][4] by the theoretical model developed by Boley et al 5 and Tenti et al 6 In this model, information regarding the Boltzmann collision integral is obtained from transport coefficients. Pan et al successfully extended the model of Boley et al 5 to predict coherent Rayleigh-Brillouin scattering ͑CRBS͒ and reported good agreement with experimental data on several monatomic and molecular gases.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed Rb-HSRL is simulated by calculating all relevant range dependent quantities and applying them to a normalized backscatter spectrum for aerosols (which are assumed to be 1000 times more massive than air molecules), and a temperature and pressure dependent molecular spectrum [7]. The subsequent backscatter spectrum is then multiplied by the relevant receiver filter function (etalon for the total channel, and etalon with rubidium spectra for the molecular channel).…”
Section: Simulationmentioning
confidence: 99%
“…The results indicate that the longer wavelengths, in the infrared (IR) spectrum, may operate in the hydrodynamic region, where λ is larger than the mean free path in the air [9], [7]. In this region the return signal is not purely Rayleigh; The return spectra has contributions from the Rayleigh and spontaneous Brillouin backscatter signal, known as spontaneous Rayleigh-Brillouin (SRB), resulting in a triplet of peaks in the spectra.…”
Section: Spontaneous Rayleigh-brillouin (Srb)mentioning
confidence: 99%
“…The added benefit of LS curve fitting is the potential for extracting other parameters (e.g., atmospheric pressure) from the estimated spectra [7]. Following Tenti's S6 theory [9], the spectra associated with the SRB backscatter for λ = 1560 nm (at two different heights in reference to sea level) has been calculated and shown in Fig. 2.…”
Section: Spontaneous Rayleigh-brillouin (Srb)mentioning
confidence: 99%